Art Has Returned: Peter Cook and His Pedagogical Practice at London Architectural Association at the Turn of the 1970s‑1980s - Malich, Ksenia A. (Actual Problems of Theory and History of Art, 2020)
The research deals with the question of new pedagogical programs elaborated at one of the leading European architectural schools — London Architectural Association — during the period of the 1970s‑1980s. Architects who graduated from the Association have become true heroes of contemporary architecture. The list of names connected with the Association is unbelievably representative: Ron Arad, Ben van Berkel, David Chipperfield, Nigel Coates, Peter Cook, Mark Fisher, Zaha Hadid, David Green, Nicholas Grimshaw, Steven Holl, Rem Koolhaas, Leon Krier, Daniel Libeskind, Richard Rogers, Patrik Schumacher, Bernard Tschumi, Elia Zenghelis. The paper is focusing on works and pedagogical methods of Peter Cook, one of Archigram leaders and Architectural Association tutors. Among the questions considered in the paper are futuristic utopian projects, nomadic cities, reprogramming of the city environment, and actualizing of medieval urbanistic models.The paper is based on the materials of the London Architectural Association archive.
Keywords: Modernism; Postmodernism; Architectural Association; Peter Cook; urbanism; contemporary architecture; London